Prevention of alcohol withdrawal syndrome in the surgical ICU: an American Association for the Surgery of Trauma Critical Care Committee Clinical Consensus Document - Christopher P Michetti; Bryce Robinson; Michael Steven Farrell; Dina M Filiberto; Lisa Kodadek; Anupamaa Seshadri; Rachel Appelbaum; Samuel P Carmichael; Randeep Jawa; Samuel Mandell; M Victoria P Miles; Jasmeet Paul (Trauma Surgery & Acute Care Open)
Alcohol withdrawal syndrome is a common and challenging clinical entity present in trauma and surgical intensive care unit (ICU) patients. The screening tools, assessment strategies, and pharmacological methods for preventing alcohol withdrawal have significantly changed during the past 20 years. This Clinical Consensus Document created by the American Association for the Surgery of Trauma Critical Care Committee reviews the best practices for screening, monitoring, and prophylactic treatment of alcohol withdrawal in the surgical ICU.